Особливості і перспективи використання концепції Веб 3.0 - Хміль, Ірина; Пащак, Мар’яна (Видавництво Львівської політехніки, 2013)
Today conception of Web 3.0 acquires all greater application in the global environment of WWW. As researchers determine, Semantic Web is approach in development of Web, that consists in filling of Web-content the specific meta data with the aim of implementation of difficult searching tasks.
Keywords: Веб 3.0; семантичний веб; мобільний веб; колективний розум; 3D-технології